Management Scheme in the Management of Al-Quran Waqf Funds at the Medan Al-Quran Wakaf Board - Suganda, Bobby Anasta; Haikal, Muhammad Fachran (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research discusses the fund management of the Medan Al-Quran Waqf Board. It also analyses the programmes of the Al-Quran Waqf funds and the factors that support and hinder the process of fund management. In this research, the focus is given on how the management of funds in the Al-Quran Waqf Board. This research was conducted in Medan Al-Quran Waqf Board. In this research, the author uses the type of field research which is by looking for data in the field in detail and detail by observing the phenomena that exist in the field. The method used in this research is a qualitative data research method, where data collection is carried out through observation, interviews and documentation studies related to the Al-Quran Waqf Board. The collected data will be analysed to identify improvements in the management of the Al-Quran Waqf Fund. The results of this study are expected to provide insight, especially about the management scheme in the management of funds in the Al-Quran Waqf Agency. Based on the results of the research, the strategy adopted by the Medan Al-Quran Waqf Board in the process of managing funds is by explaining the objectives through presentations in offices and mosques, opening outlets around mosques and offices and also making charity boxes. In addition, the BWA has a team whose job is to explore the house to collect waqf funds, and the BWA has an official website that accepts online donations through its official website, BWA.id. The facilitating factors in fund management are the cooperation of the Medan Al-Quran Waqf Board with offices and mosques, and obtaining permission to manage waqf funds. The inhibiting factors in the process of managing waqf funds are the lack of human resources, the lack of permission to cooperate, the remote location of fund management, the lack of knowledge about waqf and the poor perception of the community. The answer to these problems is that the BWA must be able to convince the public about waqf so that the funds can be properly managed.